How a Buddha Acts: Laying Bricks for a Buddhist Theory of Action - Maithani, Mukund (Stance: an international undergraduate philosophy journal, 2022)
Buddhist philosophers generally hold that concepts like “I” and “me,” while useful in everyday life, are ultimately meaningless. Under this view, there would be no “agents” because it is meaningless to say “I did so and so....” How do we explain the occurrence of actions without referring to agents? I argue that Cappelen and Dever’s Action Inventory Model (AIM) is a useful resource for developing a Buddhist theory of action. In response to an objection that AIM cannot explain a buddha’s action, I show that a slightly tweaked version of AIM succeeds in explaining how a buddha acts.